Difference and Disdain as Indicators of the Public Stigma of Mental Illness. Issue 9 (4th September 2021) - Corrigan, Patrick W.; Talluri, Sai Snigdha; Qin, Sang
Abstract: Viewing a stigmatized group as different from everyone else is believed to be a contentless stigma that leads to disdain. This study tests whether three emotions—intergroup anxiety, anger, and empathy—mediate the path between difference and disdain. Six hundred thirty-eight research participants from MTurk provided valid responses to an online survey via Qualtrics. The survey used standardized measures of difference, disdain, intergroup anxiety, anger, and empathy. The hypothesized path model was tested using structural equation modeling (SEM). Fit indicators from SEM and corresponding betas supported a two-mediator model. Specifically, difference was found to be significantly associated with disdain. The path between the two was positively mediated by anger and negatively mediated by empathy. Difference and disdain may become important constructs in predicting and assessing stigma change. Perspective-taking that enhances empathy may prove especially useful for decreasing difference and disdain perceptions about people with mental illness.